2021
DOI: 10.1161/strokeaha.120.033374
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Attenuated Inversion Recovery May Serve As a Tissue Clock in Patients Treated With Endovascular Thrombectomy

Abstract: Background and Purpose: We investigated whether the signal change on fluid-attenuated inversion recovery (FLAIR) can serve as a tissue clock that predicts the clinical outcome after endovascular thrombectomy (EVT), independently of the onset-to-admission time. Methods: Consecutive patients with acute stroke treated with EVT between September 2014 and December 2018 were enrolled. Based on the parenchymal signal change on FLAIR, patients were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The mean age of included subjects was 71.8 ± 12.8 years, 123 (55%) were male, and the baseline NIHSS score was a median of 11 [IQR,[6][7][8][9][10][11][12][13][14][15][16][17][18]. All images were taken in the following order: NCCT -DWI -FLAIR, starting after a median of 139 min after the time of the last known well.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean age of included subjects was 71.8 ± 12.8 years, 123 (55%) were male, and the baseline NIHSS score was a median of 11 [IQR,[6][7][8][9][10][11][12][13][14][15][16][17][18]. All images were taken in the following order: NCCT -DWI -FLAIR, starting after a median of 139 min after the time of the last known well.…”
Section: Resultsmentioning
confidence: 99%
“…The safety and efficacy of intravenous thrombolysis based on the DWI-FLAIR mismatch were documented in randomized clinical trials ( 11 , 12 ). A single-center study showed the utility of the DWI-FLAIR mismatch as a case selection for endovascular recanalization treatment ( 10 ). Therefore, DWI-FLAIR mismatch may be considered a tissue clock, beyond the role of a time clock, that may guide the reperfusion treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively high percentage of combined mechanical thrombectomy (35%) might be one of the reasons for the preferable outcomes in our patients. Aoki et al [11] recently demonstrated that DWI-FLAIR mismatch was independently associated with mRS 0–1 at 3 months after mechanical thrombectomy. Therefore, MRI-guided selection may also help in selecting candidates for mechanical thrombectomy.…”
Section: Discussionmentioning
confidence: 99%